THE ROLE OF CIRCLE ART IN THE AESTHETIC EDUCATION OF YOUNG PEOPLE - Nazarov Sherzod Dilshod ugli (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, analytical comments are made on the origin of the instrument of the Uzbek national musical circle and its role in the Uzbek national culture and art, its development, the factors of gradual development, the achievements of Master Musicians in the performance of the circle and the importance of this instrument in the present day.